Proceedings of the International Grid-Connected Renewable Energy Policy Forum - World Bank (World Bank, Washington, DC, 2014)
This document presents the highlights of speaker presentations, breakout groups, ensuing discussions, conclusions, and next steps as presented at the International Grid- Connected Renewable Energy (RE) Policy Forum. The conferences purpose was to facilitate increased use of grid-connected RE in the developing world. In the course of the three-day meetings, speakers and participants addressed the challenge of scaling up the use of RE for grid power supply. The interactive forum was designed to focus on four core topics: 1) incorporation of RE in power sector frameworks; 2) economic valuation of RE; 3) RE policy instruments; and 4) private sector investment in RE. The forum also presented issues and offered solutions, lessons learned, best practices, and country-specific case studies